THE EFFECT OF THE RECIPROCAL TEACHING METHOD ON STUDENTS READING COMPREHENSION - Putri Mareza; Destri Wahyuningsih; Widi Syaftinentias (Program Studi Pendidikan Bahasa Inggris, 2026)
Reading comprehension is an important skill in English learning because it helps students understand information and improve critical thinking. However, many students still face difficulties in understanding texts due to low reading interest and the use of less interactive teaching methods. This study aimed to determine the effect of the Reciprocal Teaching Method on students’ reading comprehension at the tenth grade of SMK N 1 Kelayang. This research used a quantitative experimental method with two groups: an experimental class and a control class. The sample consisted of 43 students. The data were collected through pre-test and post-test and analyzed using descriptive statistics and t-test. The findings showed that the students taught by using the Reciprocal Teaching Method achieved higher reading comprehension scores than those taught by conventional methods. The mean score of the experimental class increased significantly after the treatment. It can be concluded that the Reciprocal Teaching Method had a significant effect on students’ reading comprehension. Therefore, this method is recommended for English teachers to improve students’ reading comprehension skills.